2018
DOI: 10.1108/ajar-07-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Transparency of local government in Indonesia

Abstract: Purpose -The purpose of this paper is to provide empirical evidence about the influence of the size of local government, the quality of local government financial statements, the level of local government response to the disclosure of financial information and the local political environment on the transparency of local government in Indonesia. Design/methodology/approach -The study sample consisted of 34 regional governments (provinces) in Indonesia in 2016, using purposive sampling and multiple regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 15 publications
1
42
1
10
Order By: Relevance
“…The government provides detailed and essential information and maintains public access (Tavare and da Cruz 2017). Adiputra et al (2018) said that one of the problems affecting communities is the lack of accessibility to government-held information. Due to the correlation between responsibility and ethical issues, corruption, bureaucracy, obligations or inertia bureaucracy (Purnomo et al, 2019), transparency is one of the key aspects of good governance in ensuring access for all, including public expenditure management, information on governance (Medina, 2012).…”
Section: Transparency and Accountabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The government provides detailed and essential information and maintains public access (Tavare and da Cruz 2017). Adiputra et al (2018) said that one of the problems affecting communities is the lack of accessibility to government-held information. Due to the correlation between responsibility and ethical issues, corruption, bureaucracy, obligations or inertia bureaucracy (Purnomo et al, 2019), transparency is one of the key aspects of good governance in ensuring access for all, including public expenditure management, information on governance (Medina, 2012).…”
Section: Transparency and Accountabilitymentioning
confidence: 99%
“…IT equipment can change from traditional management to modern management to increase financial statements' efficiency and significance (Jiang 2020). In this regard, Adiputra et al (2018) and Ode Hasiara (2017) suggested using a management information system that can explain the financial reporting of local government. Financial technology's use and development have influenced many people and many communications (ICT) in everyday life (Afroz, Muhibbullah, and Morshed, 2020).…”
Section: Transparency and Accountabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to understand that the provision of necessary and desired information in accordance with the expectations of the public today is the government's obligation in order to fulfill the rights the citizens deserve. It is the duty of policymakers and officials to jointly participate in creating conditions for good governance that are a necessity in today's global society, which inevitably encourages governments to be open and transparent to meet the demands of our increasingly developed and modern society by making responsible, transparent, open government as a form of democratic and accountable government system (Weil et al, 2006;Hood & Heald, 2006;Hollyer et al, 2014;Adiputra et al, 2018).…”
Section: Introductionmentioning
confidence: 99%